2013
DOI: 10.1002/rmv.1776
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of severe fever with thrombocytopenia syndrome:virology, epidemiology, and clinical characteristics

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) was firstly discovered in China in 2010, followed by several reports from many other countries worldwide. SFTS virus (SFTSV) has been identified as the causative agent of the disease and has been recognized as a public health threat. This novel Bunyavirus belongs to the Phlebovirus genus in the family Bunyaviridae. This review also describes the different aspects of virology, pathogenesis, epidemiology, and clinical symptoms on the basis of the published artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(175 citation statements)
references
References 53 publications
6
168
1
Order By: Relevance
“…Our study showed that the seropositivity rate of SFTSV-IgG antibodies among participants in Yixian country was 6.3%, which was higher than the reported rate of 4.66% in endemic areas of Anhui Province (21). This discrepancy may be related to the number involved, age, sex, geographic location, and types of antibodies tested (total antibodies or IgG antibodies against SFTSV) (22).…”
Section: Discussioncontrasting
confidence: 76%
“…Our study showed that the seropositivity rate of SFTSV-IgG antibodies among participants in Yixian country was 6.3%, which was higher than the reported rate of 4.66% in endemic areas of Anhui Province (21). This discrepancy may be related to the number involved, age, sex, geographic location, and types of antibodies tested (total antibodies or IgG antibodies against SFTSV) (22).…”
Section: Discussioncontrasting
confidence: 76%
“…It has a seasonal occurrence from May to September and mainly targets those of ! 50 years of age (2). Cases of SFTS in Japanese patients with a higher fatality rate (55%) are very similar to the severe cases reported in Chinese patients (3), however, there have been only three published autopsy cases reporting pathological analyses for the disease progression to death of SFTS (3,4).…”
Section: Introductionsupporting
confidence: 61%
“…dengue (30%), malaria (20.83%), enteric fever (5%) HIV (4.16%) followed by megaloblastic anemia (21.66%). Similar findings were also noted in systematic review by Liu Shelan et al 7 In our study, 25 patients (20.83%) received blood transfusion out of that 14 patients had platelet count less than 10000/mm 3 and 11 patients had platelet count more than 10000/mm 3 . In our study we had noted highest and lowest platelet count in male and female patient but there was no significant difference between sex and platelet count.…”
Section: Discussionsupporting
confidence: 91%